1990
DOI: 10.1111/j.1476-5381.1990.tb12110.x
|View full text |Cite
|
Sign up to set email alerts
|

CI‐977, a novel and selective agonist for the κ‐opioid receptor

Abstract: (DPDPE) labelled 6-sites (Ki = 1.O4pM). CI-977 also bound with negligible affinity to [3H]-(+ )3-(1-propyl-3-piperidinyl)phenol (3-PPP) labelled a-sites (Ki = 1.9jUM) and C3H]-141-[2-thienyl]cyclohexyl)piperidine (TCP) labelled PCP sites (Ki > 10pM).3 CI-977 produced a potent inhibition of the electrically-evoked contractions of the guinea-pig ileum and rabbit vas deferens with IC5o values of 0.087nm and 3.3nm, respectively. The pK5 values for the opioid antagonists naloxone (7.6) and norbinaltorphimine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(63 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…Centrally-acting K-opioid receptor agonists generally induce sedative effects at higher doses than central antinociceptive actions (Hayes et al, 1990;Hunter et al, 1990). The three K agonists we tested were effective in the rodent writhing test (Figure 3), and the present ID50 values for ICI 197067 and ICI 204448 in the mouse writhing test (0.02 and 1.9 mg kg-', s.c., respectively) are in good agreement with those published previously by others (0.05 (0.02-0.06) and 4.4 (2.5-7.4)mgkg-', s.c., respectively; Costello et al, 1988;Rogers et al, 1992).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Centrally-acting K-opioid receptor agonists generally induce sedative effects at higher doses than central antinociceptive actions (Hayes et al, 1990;Hunter et al, 1990). The three K agonists we tested were effective in the rodent writhing test (Figure 3), and the present ID50 values for ICI 197067 and ICI 204448 in the mouse writhing test (0.02 and 1.9 mg kg-', s.c., respectively) are in good agreement with those published previously by others (0.05 (0.02-0.06) and 4.4 (2.5-7.4)mgkg-', s.c., respectively; Costello et al, 1988;Rogers et al, 1992).…”
Section: Discussionmentioning
confidence: 89%
“…We found that the action of EMD 60400 in these tests could be reversed by pretreatment with naloxone (1 mg kg-', s.c.), like Hunter et al (1990) who found that this dose of naloxone completely antagonized antinociception produced by CI-977, PD 117302, U 69593, U 50488 and other K-agonists in the rat paw pressure test. The observation that the action of EMD 60400 in the hyperalgesic pressure pain test can be completely antagonized by 0.2 mg kg-' naloxone s.c. may, however, indicate that this compound can also have activity at t-opioid receptors under some in vivo experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the acute effects of the arylacetamide, enadoline, were examined. Like Mr2034, enadoline has high efficacy at k receptors, but it differs in that it also is highly selective for k receptors (Hunter et al, 1990). Both Mr2033 and enadoline dose dependently decreased cocaine self-administration during chronic treatment (Mello and Negus, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One reliable physiological indicator of kappa receptor activation is the production of diuresis. Increased urinary output has been observed after administration of selective kappa agonists, such U50,488 (Vonvoigtlander et al 1983), enadoline (CI-977) (Hunter et al 1990;Leander et al 1985), spiradoline (Rimoy et al 1991), and ethylketocyclazocine (Slizgi and Ludens 1982). The findings with butorphanol on urinary outcomes have been mixed.…”
mentioning
confidence: 99%